Intravenous SPION-labeled adipocyte-derived stem cells targeted to the brain by magnetic attraction in a rat stroke model: An ultrastructural insight into cell fate within the brain - García-Belda, Paula; Prima-García, Helena; Aliena-Valero, Alicia; Castelló-Ruiz, María; Ulloa-Navas, María José; Ten-Esteve, Amadeo; Martí-Bonmatí, Luis; Salom, Juan B.; García-Verdugo, José Manuel; Gil-Perotín, Sara (Nanomedicine, 2022)
Mesenchymal stem cell therapy after stroke is a promising option investigated in animal models and clinical trials. The intravenous route is commonly used in clinical settings guaranteeing an adequate safety profile although low yields of engraftment. In this report, rats subjected to ischemic stroke were injected with adipose-derived stem cells (ADSCs) labeled with superparamagnetic iron oxide nanoparticles (SPIONs) applying an external magnetic field in the skull to retain the cells. Although most published studies demonstrate viability of ADSCs, only a few have used ultrastructural techniques. In our study, the application of a local magnetic force resulted in a tendency for higher yields of SPION-ADSCs targeting the brain. However, grafted cells displayed morphological signs of death, one day after administration, and correlative microscopy showed active microglia and astrocytes associated in the process of scavenging. Thus, we conclude that, although successfully targeted within the brain, SPION-ADSCs viability was rapidly compromised. Rats subjected to ischemic stroke by transient middle cerebral occlusion (tMCAo) were injected with adipose-derived stem cells (ADSCs) labeled with superparamagnetic iron oxide nanoparticles (SPIONs) applying an external magnetic field in the skull to retain the cells. The application of a local magnetic force resulted in a tendency for higher yields of SPION-ADSCs targeting the brain. However, grafted cells displayed morphological signs of death, one day after administration, and correlative microscopy showed active microglia and astrocytes associated in the process of scavenging. [Display omitted] •SPION-labeled ADSCs preserve viability, morphology and mesenchymal stem cell features.•SPION-ADSCs behave as superparamagnetic cells.•Local magnetic force retains intravenous SPION-ADSCs in the stroke damaged brain.•Grafted SPION-ADSCs are subject of precocious cell death and phagocytosis by glia.